The relationship between Interleukin-27 gene polymorphisms and Kawasaki disease in a population of Chinese children. (5th July 2018) - Si, Feifei; Wu, Yao; Wang, Xianmin; Gao, Fang; Yang, Dan; Liu, Ruixi; Yi, Qijian
Abstract: Background: Kawasaki disease is the leading cause of acquired heart disease in children from developed countries. The Interleukin-6/ Interleukin-12 cytokine family has many members, including the paradoxical anti- and pro-inflammatory Interleukin-27. Recent studies have demonstrated that Interleukin-27 plays a role in immune diseases. Given this, we sought to evaluate the association between Interleukin-27 genetic polymorphisms and Kawasaki disease in Chinese children. Methods and results: Interleukin-27 was genotyped in 100 Kawasaki disease children and 98 healthy children (controls), resulting in the direct sequencing of eight Single-nucleotide Polymorphisms: rs17855750, rs40837, rs26528, rs428253, rs4740, rs4905, rs153109, and rs181206). There were no significant differences in Interleukin-27 genotypes between Kawasaki disease and control groups. Of the eight Single-nucleotide Polymorphisms, there was a significant increase in the risk of Kawasaki disease with coronary arterial lesions in children with the rs17855750 (T>G), rs40837 (A>G), rs4740 (G>A), rs4905 (A>G), rs153109 (T>C), and rs26528 (A>G) Single-nucleotide Polymorphisms. This was particularly true for rs17855750 (T>G), which had a greater frequency in Kawasaki disease children with coronary arterial aneurysm. Conclusion: These findings may be used as risk factors when assessing a child's likelihood of developing Kawasaki disease, as well as for the development of future therapeutic treatments for Kawasaki disease.